2021
DOI: 10.1136/bmjopen-2020-039809
|View full text |Cite
|
Sign up to set email alerts
|

Conversations about FGM in primary care: a realist review on how, why and under what circumstances FGM is discussed in general practice consultations

Abstract: ObjectivesLittle is known about the management of female genital mutilation (FGM) in primary care. There have been significant recent statutory changes relevant to general practitioners (GPs) in England, including a mandatory reporting duty. We undertook a realist synthesis to explore what influences how and when GPs discuss FGM with their patients.SettingPrimary care in England.Data sourcesRealist literature synthesis searching 10 databases with terms: GPs, primary care, obstetrics, gynaecology, midwifery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 127 publications
0
12
0
1
Order By: Relevance
“…When the GPs did not ask them about-or link their health problems to-FGC, participants mostly concluded that the GPs lacked knowledge of FGC or that their health problems were not FGC-related. We do not know the GPs' exact reasons for not asking about FGC, but former findings [60][61][62] suggest that perceiving FGC as a taboo and having insufficient knowledge may play a key role. In several Western countries, GPs score low on both the clinical and cultural aspects of FGC [63][64][65].…”
Section: Discussionmentioning
confidence: 89%
“…When the GPs did not ask them about-or link their health problems to-FGC, participants mostly concluded that the GPs lacked knowledge of FGC or that their health problems were not FGC-related. We do not know the GPs' exact reasons for not asking about FGC, but former findings [60][61][62] suggest that perceiving FGC as a taboo and having insufficient knowledge may play a key role. In several Western countries, GPs score low on both the clinical and cultural aspects of FGC [63][64][65].…”
Section: Discussionmentioning
confidence: 89%
“…The lead reviewers on each project agreed to contribute their data to this study. The detailed methods employed in each review are reported in their own study protocols and published reports (where applicable) 39–48 . For this study, we collected data from each review team relating to the final list of documents included in each review.…”
Section: Methodsmentioning
confidence: 99%
“…In our work on endometriosis 12 and female genital mutilation (FGM), 13 14 we found that the majority of evidence deployed in primary care is derived from specialist settings and then extrapolated back to the primary care setting, where the populations and needs may significantly differ.…”
Section: Lack Of Research On Women’s Health In Primary Carementioning
confidence: 99%
“…Another example is the predominance of FGM research in obstetric and midwifery settings resulting in a lack of evidence or resources for how GPs might support women with FGM beyond their reproductive years and through the menopause. 14 Where potential gaps in care are identified, all too often the conclusion is that GPs lack knowledge and awareness, and that increasing these would improve care. 12 However, our work on endometriosis demonstrates GPs are rarely working with a lack of knowledge, but rather engage with complex and nuanced considerations.…”
Section: Lack Of Research On Women’s Health In Primary Carementioning
confidence: 99%